Agricultural Productivity Shocks, Labor Reallocation, and Rural-Urban Migration in China - Luigi Minale (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2018)
This paper analyses the way households in rural China use rural-urban migration and off-farm work as a response to negative productivity shocks in agriculture. I employ various waves of a longitudinal survey to construct a panel of individual migration and labour supply histories, and match them to detailed weather information, which I use to instrument agricultural productivity. For identification, I exploit the year-by-county variation in growing season rainfalls to explain within-individual changes in labor allocation. Data on days of work supplied to each sector allow to study the responses to weather shocks along both the participation and the intensive margin. Results suggest that farming activity decreases by 4.5% while migration increases by about 5% in response to a 1-standard deviation negative rainfall shock. Increment in rural-urban migration derives from both longer spells in the city as well as raise in the likelihood to participate in the urban sector. I find interesting heterogeneous responses across generations driven by age-specific migration costs and changes in the relative productivity of sectors. Finally, land tenure insecurity seems to partially prevent households from freely reallocating labor away from farming in bad times.
Keywords: J22; R23; J61; 330; Agricultural productivity; Labor supply; Rural-urban migration; China